Mengoptimalkan Efektivitas Kegiatan Keagamaan di Dusun Sanggrahan Ampelgading Tirtoyudo - Usrin Malikha (Lembaga Penelitian, Pengembangan dan Pengabdian Kepada Masyarakat (LP3M), 2022)
Sanggrahan is administratively located in Ampelgading Village, Tirtoyudo District. In this area there are several Qur'an Reading Education Parks (TPQ), namely TPQ Ar-Rohman, TPQ Nurul Hidayah, TPQ Nurus Syafi, TPQ Al Muttaqin and Madin Nurul Jadid. This place of religious learning becomes a facilitator for children in developing reading and writing of the Qur'an or other religious fields such as the practice of prayer or basic worship arrangements in carrying out routines. On the other hand, there is a lack of interest from children or support from parents, this is due to a lack of knowledge about the importance of worship or a lack of government officials, both in general and religious education. The existence of good natural potential and human resources that can still be optimized encourage students in Ampelgading to overcome the obstacles by conducting socialization of religious activities. The target of this service activity is the residents of Sanggrahan, Ampelgading Village, Tirtoyudo District, Malang. The approach method was carried out using surveys and participatory approaches in the Sanggrahan area to see the real conditions on the ground, then preparation and implementation of FGDs were carried out with local residents to plan the implementation of activities, and then preparations for program assistance. The target is expected to acquire adequate knowledge and skills.